Narrative inquirers in the midst of meaning-making interpretive acts of teacher educators - Chan, Elaine; Keyes, Dixie; Ross, Vicki (Bingley, U.K. : Emerald, 2012)
Narrative Inquirers in the Midst of Meaning-making: Interpretive Acts of Teacher Educators illustrates interim narrative field texts of identity as 'teacher educator stories' and demonstrates how researchers utilize common places of temporality, sociality, and place in analyzing narratives. It describes conceptualizations of narrative research processes, bringing forward narrative tools and methods of layering narratives from experienced narrative researchers. Through the metaphor of braided rivers, the chapters are woven together through unique chapter interim dialogues which spotlight the insights discovered within the three-dimensional inquiry space. From chapters on the temporal dimension of narrative inquiry, on burrowing and broadening through narrative, on openness and inconclusivity in interpretation, on plotlines discovered through the interpretive tool of chronotypes, and on the cross-cultural interpretation of field texts, researchers and teacher educators can reach new conclusions about the ontology and epistemology of narrative research, in the midst of meaning-making.
Foreword : creating openings to ponder interpretation, inconclusivity, and the geography of narrative / Mary Lynn Hamilton -- Introducing braided rivers / Dixie Keyes, Vicki Ross, Elaine Chan -- ch. 1. Openness and inconclusivity in interpretation in narrative inquiry : dimensions of the social/personal / Stefinee Pinnegar, Mary Lynn Hamilton -- ch. 2. Burrowing and broadening in the storied place of teacher education / Dixie Keyes, Cheryl Craig -- ch. 3. Attending to the temporal dimension of narrative inquiry into teacher educator identities / M. Shaun Murphy, Vicki Ross, Janice Huber -- ch. 4. Exploring chronotopic shifts between known and unknown in our teacher educator identity narratives / Mary Rice, Cathy Coulter -- ch. 5. Cross-cultural interpretation of field texts / Candace Schlein, Elaine Chan -- Headwaters and tributaries : meaning-making using the three-dimensional narrative inquiry space / Vicki Ross, Elaine Chan, Dixie Keyes -- Afterword : reflections on narrative inquiries into teacher education identity making / D. Jean Clandinin.
Print version record
Keywords: Education -- Teaching Methods & Materials -- Social Science; Education -- Research; Social Science -- Research; Teacher training; Research methods: general; Education -- Research -- Methodology; Narrative inquiry (Research method)